Effects of Decentralised Bargaining on Gender Inequality: Italy - Cardinaleschi, Stefania; De Santis, Stefano; Schenkel, Marina (Panoeconomicus, 2019)
This paper analyses the relation between bargaining regimes and the gender wage gap (GWG), identifying the contribution of individual characteristics. First, a description of the gender disparities in the Italian labour market is presented, using the evidence from the Linked Employer Employees Data from the Structure of Earnings Survey (SES). Then, with a particular focus on the different types of collective agreements, various decomposition techniques are employed in order to describe how gender inequality differs across bargaining regimes. Finally, some suggestions are advanced regarding the mix of policies that could reduce the gender wage gap in the labour market. Key words: Gender wage gap, Segregation, Decomposition. JEL: I26, J16, J24. Efekti decentralizovanog pregovaranja na rodnu nejednakost: Italija U radu se analizira odnos između pregovaračkih režima i jaza u platama na osnovu pola (GVG), identifikujući doprinos pojedinih karakteristika. Prvo, predstavljen je opis polnih razlika na italijanskom tržištu rada, koristeći dokaze iz podataka o odnosu radnika i poslodavaca iz Ankete o strukturi zarada (SES). Zatim, sa posebnim osvrtom na različite vrste kolektivnih ugovora, koriste se različite tehnike dekompozicije kako bi se opisalo kako se polna nejednakost razlikuje po režimima pregovaranja. Konačno, neki predlozi su unapređeni u vezi sa primenom različitih politika koje bi mogle smanjiti jaz između plata na osnovu pola na tržištu rada. Ključne reči: Jaz između plata na osnovu pola, odvajanje, dekompozicija.